2021
DOI: 10.1177/0300060520986291
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous sinus thrombosis in a young child with acute lymphoblastic leukemia: a case report and literature review

Abstract: Acute lymphoblastic leukemia (ALL) is a hematological malignancy. There are many risk factors for thrombus development in patients with ALL, and thrombi may develop in different parts of the body. Cerebral venous sinus thrombosis (CVST) is a rare complication of ALL that usually appears during treatment. We present a patient who developed CVST twice, once before diagnosis and once after treatment for ALL. We also reviewed the literature describing ALL and CVST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Clinical findings of thrombosis may be confusing with drug-related neurologic side effects and symptoms of CNS involvement in ALL. 4,26 In our study, headache, seizure, and alternating consciousness were the most common clinical symptoms in patients with CNS thrombosis. However, different neurological symptoms such as vomiting, vision and speech disorder, facial paralysis, hemiparesis, weakness, personality changes, dizziness, and numbness in the extremities were observed at varying rates.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Clinical findings of thrombosis may be confusing with drug-related neurologic side effects and symptoms of CNS involvement in ALL. 4,26 In our study, headache, seizure, and alternating consciousness were the most common clinical symptoms in patients with CNS thrombosis. However, different neurological symptoms such as vomiting, vision and speech disorder, facial paralysis, hemiparesis, weakness, personality changes, dizziness, and numbness in the extremities were observed at varying rates.…”
Section: Discussionmentioning
confidence: 52%
“…Clinical findings of thrombosis may be confusing with drug‐related neurologic side effects and symptoms of CNS involvement in ALL 4,26 . In our study, headache, seizure, and alternating consciousness were the most common clinical symptoms in patients with CNS thrombosis.…”
Section: Discussionmentioning
confidence: 60%
“…The risk of thrombosis increases by eight times if only one thrombophilia factor is present [ 9 ]. Our patient’s recent asparaginase treatment placed him at an increased risk of CVST, as asparaginase chemotherapy causes natural anticoagulant deficiency [ 10 ]. So, this shifts our minds from considering direct infiltration as the primary cause of retinal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was stopped as well, and a repeated CT brain was performed after one month of stopping the treatment showing normal results [ 5 ]. Similarly, Liu et al stopped the asparaginase therapy when their patient developed severe thrombosis and signs of CVST [ 10 ]. Additionally, another study concluded that receiving less asparaginase therapy improves the outcomes substantially [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asparaginase and steroids are significant risk factors for venous thromboembolism (VTE), as they interfere with levels of natural anticoagulants leading to suboptimal treatment responses in ALL patients, and there are currently no proven preventive strategies for VTE during ALL treatment [ 69 , 70 , 71 ]. Antibodies to asparaginase lead to disease relapse [ 72 ].…”
Section: Reviewmentioning
confidence: 99%